Frequency and trend of dengue fever in a tertiary care hospital in Kancheepuram, Tamilnadu: three-year retrospective study - M., Vijayakarthikeyan (International Journal Of Community Medicine And Public Health, 2020)
Background: Dengue is a mosquito borne viral disease which is endemic in the tropical and subtropical regions. In the recent years it has become a significant public health problem and its incidence is increasing in India. In 2016 1.1 lakh new dengue cases were reported in India. The objectives of the study was to describe the frequency and distribution of dengue infection and to determine the association between dengue infection and selected variables. Methods: The study is a hospital based retrospective study conducted in a tertiary care hospital in a rural area of Kancheepuram district. Three-year data (January 2015 to December 2017) was collected from the medical records department of the hospital. Dengue cases were diagnosed by ELISA test. Results: Among 340 dengue patients admitted in the hospital 240 (74.5%) were male and 100 (25.5%) were female. In this study, 306 (90%) patients were of the classical dengue type and 34 (10%) patients belong to dengue haemorrhagic fever type. There is a spike in the case load after the monsoons. There was a positive statistical significant association (p<0.0001) between dengue infection and male sex, low socioeconomic status and platelet count at the time of admission. Conclusions: Results of the study indicate that there should be proper education of the public through various available Medias and awareness campaigns. All dengue patients must be appropriately treated in order to prevent complications. The national vector borne disease control program must extend its coverage to combat dengue infection.